The Quality of Life and Functional Outcome of Hindfoot Reconstructive Surgery in Charcot Foot - Zainudin, Mohd Hijaz; Ayeop, Mohd Adham Shah; Ahmad, Aminudin Che (IIUM Medical Journal Malaysia, 2018)
Introduction: Charcot foot problem is devastating and a difficult condition to treat. There are limited data and study regarding the quality of life and functional outcome of Charcot foot being treated surgically. This study evaluates the outcome of Charcot foot treated with reconstructive surgery. Materials and Methods: This is a cross-sectional study that compares the quality of life and functional outcome of patient with Charcot foot pre and post tibio-talar-calcaneal (TTC) arthrodesis surgery at Hospital Tengku Ampuan Afzan and International Islamic University Malaysia Medical Centre between 2016 and 2018. Patients were evaluate using SF-36 scores and AOFAS scores pre and post-operative at average of 6 months (range between 3 to 9 months). Results: Thirty patients had undergone reconstructive foot and ankle surgery using hindfoot arthrodesis nail (HAN) for TTC arthrodesis. The outcome was assessed using paired t-test comparing pre and postoperative for both SF-36 and AOFAS scores. The SF-36 components had significant improvement with a mean of 35 to 45.6 for physical component (PCS) and 46.6 to 52.5 for mental component (MCS) (p<0.0001). The overall AOFAS score had significant improvement from average of 36 to 57.8 out of 100 (p<0.0001). Pain component of AOFAS shows lower score of improvement. Two patients had suffered ulceration post operatively that requires multiple debridement and exostectomy with one patient requires removal of HAN eventually. Conclusions: Tibio-talo-calcaneal arthrodesis using HAN surgery improves the quality of life and functional outcome of Charcot foot.